Feasibility of visual instrumented movement feedback therapy in individuals with motor incomplete spinal cord injury walking on a treadmill - Schließmann, Daniel; Schuld, Christian; Schneiders, Matthias; Derlien, Steffen; Glöckner, Maria; Gladow, Till; Weidner, Norbert; Rupp, Rüdiger (Frontiers in Human Neuroscience, 2014)
Background: Incomplete spinal cord injury (iSCI) leads to motor and sensory deficits. Even in ambulatory persons with good motor function an impaired proprioception may result in an insecure gait. Limited internal afferent feedback (FB) can be compensated by provision of external FB by therapists or technical systems. Progress in computational power of motion analysis systems allows for implementation of instrumented real-time FB. The aim of this study was to test if individuals with iSCI can normalize their gait kinematics during FB and more importantly maintain an improvement after therapy. Methods: Individuals with chronic iSCI had to complete 6 days (one day per week) of treadmill-based FB training with a 2 weeks pause after 3 days of training. Each day consists of an initial gait analysis followed by 2 blocks with FB/no-FB. During FB the deviation of the mean knee angle during swing from a speed matched reference (norm distance, ND) is visualized as a number. The task consists of lowering the ND, which was updated after every stride. Prior to the tests in patients the in-house developed FB implementation was tested in healthy subjects with an artificial movement task. Results: 4 of 5 study participants benefited from FB in the short and medium term. Decrease of mean ND was highest during the first 3 sessions (from 3.93±1.54 to 2.18±1.04). After the pause mean ND stayed in the same range than before. In the last 3 sessions the mean ND decreased slower (2.40±1.18 to 2.20±0.90). Direct influences of FB ranged from 60% to 15% of reduction in mean ND compared to initial gait analysis and from 20% to 1% compared to no-FB sessions. Conclusions: Instrumented kinematic real-time FB may serve as an effective adjunct to established gait therapies in normalizing the gait pattern after incomplete spinal cord injury. Further studies with larger patient groups need to prove long term learning and the successful transfer of newly acquired skills to activities of daily living.